Opinion on act (decision), adopted by the Holy Synod of the Patriarchate of Constantinople on 11 October 2018 (Stato, Chiese e pluralismo confessionale, 2019)
SUMMARY: 1. Introduction - 2. Main Part. An Examination - 3. Complete exhaustion of the subject of the executive act adopted by the Patriarchate of Constantinople in 1686 - 4. Assessment of the actions from the perspective of the legislation of the Republic of Turkey - 5. Conclusions.
Keywords: Diritto ecclesiastico comparato e straniero